Establishment of Avicennia marina mangroves on accreting coastline at Sungai Haji Dorani, Selangor, Malaysia - Tamin, N.M.; Zakaria, R.; Hashim, Roslan; Yin, Y. (2011)
Avicennia marina saplings were established within a restoration area at Sg. Hj. Dorani, Malaysia between May and August 2010. Sapling establishment was achieved following the construction of segmented and hard breakwater as mitigating measure against coastal erosion. Geostructures known as brush faschines were installed within the restoration area as secondary sediment and seed traps. There was a steady increase in the sand content of the soil from 5% in November 2008 to 18% in May 2010. The dominant soil content was silt but it fluctuated and declined slightly over the same period, between 80% in November 2008 and 72% in May 2010. The accreting shoreline behind the breakwater had stabilised within 18 months. Subsequently, the first batch of A. marina wild seedlings or wildings was established on the mud surface in September 2009. Only about 10% of these wildings survived and showed high survival rate (90%) over the next eight months. Wildings that were naturally established near mother trees showed good growth performance. No wilding was established after the fruiting season in August 2010 as all seeds that were dispersed into the restoration area were washed away by September 2010. Tall, A. marina wild saplings (1 m) planted within the restoration area showed higher survival rate (80%) compared to planted saplings of Rhizophora apiculata (30%). Final planting of a thousand 1 m tall A. marina wild saplings was carried out from June 2010, in clumps of 20 and in 1 m × 1 m spacing. By the end of September 2010 clusters of regenerating A. marina mangroves about 1.5 m tall were successfully established on the accreting coastline.